In-Habitant: An Inquiry into a Non-Dualistic Duality of Human and Nonhuman - Tasa, Umut (MIT PRESS, 2023)
In-Habitant is an art and life project based on artist Umut Tasa's decadelong encounters with urban wildlife. It is a quest to utilize art as a research method to contemplate her memories, nature discoveries, audiovisual records, and archive of haiku and prose through a body of artworks. These artworks bring together the corporeality of nonhumans with their digital re-presentation and literary text with creative coding. The author inquires into dualistic and nondualistic ontological approaches to human-nonhuman relations in urban settings.
Keywords: Art